Effects of power training on quality of life and postural stability in elderly - Tolentino, Grassyara Pinho; Soares, Viviane; Venâncio, Patrícia Espíndola Mota; Moraes, João Lucas de; Lima, Pablo Rodrigues; Filho, Ariel Vieira de Moraes; Lima, William Alves; Júnior, Jairo Teixeira; Oliveira, Deise Aparecida Almeida Pires de; Oliveira-Silva, Iransé (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The muscular strength exercises can be an effective intervention to prevent falls and to favor the functional capacity (FC) in the elderly. However, few studies have reported the benefits of power training (PT) and the subjective perception of the elderly on these activities. Objective: to evaluate the repercussions of a power training protocol on functional capacity and subjective health parameters in the elderly. Method: It was a prospective study involving 48 elderly people. Two groups were composed: a power training group (PG) with 22 participants with a mean age of 68.14 (5.46) years and the control group (CG) was composed of 32 elderly individuals aged 68.03 (4.83) years. Health-related quality of life was measured from the Medical Outcomes Study 36 – Item Short-Form Health Survey (SF-36). The FC was measured by the Berg Balance and Time Up and Go tests. The PT was performed 2x/week, with duration of 50 min/session, for 14 weeks (first two weeks of adaptation; first six weeks 3X/10-15 repetitions of 40-50% of the Subjective Perceived Exertion (SPE) / 6 following weeks 3X/6-10 repetitions of 60-70% of the SPE). The CG performed rhythm activities with the same frequency and weekly duration. Result: It was observed favorable results in FC after 14 weeks of power training. There was also a positive evaluation of most sf-36 domains, with emphasis on physical and emotional aspects. However, the perception of the elderly in relation to the pain domain presented negative results. Conclusion: The PT positively influenced the FC, the physical and the emotional aspects of the elderly; negatively affected the pain and maintained the low risk of fall after 12 weeks of intervention, without presenting intercurrences during the intervention.